From anger to solidarity: The emotional echo-chamber of Gezi park protests. (November 2019) - Eslen-Ziya, Hande; McGarry, Aidan; Jenzen, Olu; Erhart, Itir; Korkut, Umut
Abstract: By using the Gezi Park protests that took place in Turkey in 2013 as a case, we explore the significance of emotional echo-chamber involved in protests. The analyses are composed of thirty-seven interviews conducted with activists on how they define and understand their preferences and motivations for protesting. We discuss how participants get influenced by beliefs, motives and opinions and bring forth the changes of emotions during such processes and help create an emotional echo-chamber. Highlights: There is an emotional component to how people come together and take part in social movements. Emotions exist in every stage of political protest. First anger and outrage and later on a sense of belongings, pride and hope had an activating effect on the participants. Once our participants were in the park, positive emotions like pride, joy and a sense belonging seem to play an important role.